2015
DOI: 10.1039/c5ra06626c
|View full text |Cite
|
Sign up to set email alerts
|

Assisted sintering of silver nanoparticle inkjet ink on paper with active coatings

Abstract: Inkjet-printed metal films are important within the emerging field of printed electronics. For large-scale manufacturing, low-cost flexible substrates and low temperature sintering is desired. Tailored coated substrates are interesting for roll-to-roll fabrication of printed electronics, since a suitable tailoring of the ink-substrate system may reduce, or remove, the need for explicit sintering. Here we utilize specially designed coated papers, containing chloride as an active sintering agent. The built-in si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 30 publications
(39 reference statements)
0
31
0
Order By: Relevance
“…Paper‐based substrates have recently attracted increasing research and commercial interests for PE due to their natural abundance, light weight, renewability, mechanical flexibility, and nontoxicity over their counterparts . Coffee ring effect is often undesired but does exist during inkjet printing process.…”
Section: Printing Conductive Nanomaterials Inksmentioning
confidence: 99%
“…Paper‐based substrates have recently attracted increasing research and commercial interests for PE due to their natural abundance, light weight, renewability, mechanical flexibility, and nontoxicity over their counterparts . Coffee ring effect is often undesired but does exist during inkjet printing process.…”
Section: Printing Conductive Nanomaterials Inksmentioning
confidence: 99%
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 coalescence of Ag NPs. 35 Therefore, we used SEM imaging of the unprocessed CuO films to examine any possible aggregation of CuO NPs for each paper series. No difference in CuO layer morphology was noted with the different precoatings (Supporting Information, Figure S3).…”
Section: Surface Morphologymentioning
confidence: 99%
“…Recently we showed that this paper design assisted low-temperature sintering of AgNP ink. 35 Here we demonstrate that the CaCO 3 precoating enhances reliability and effectiveness during IPL processing of CuO, thereby substantially improving the performance of inkjet-printed copper films.…”
mentioning
confidence: 96%
“…In order to solve this issue, the paper substrate that we selected is provided by a CaCO 3 precoating. Ohlund et al 52,53 demonstrated that AgNP ink sintering could be impaired by the coating pore size but greatly enhanced by using a porous CaCO 3 precoating. They proved that small concentrations of Cl and Ca are present on the surface of the paper with CaCO 3 precoating, and due to the presence of Cl in the AgNP ink, low temperature sintering with high conductivity values of printed pads can be facilitated by the presence of chloride.…”
Section: Resultsmentioning
confidence: 99%